2015
DOI: 10.1007/s11695-015-1726-3
|View full text |Cite
|
Sign up to set email alerts
|

Should We Abandon Routine Microscopic Examination in Bariatric Sleeve Gastrectomy Specimens?

Abstract: Routine microscopic examination of all LSG specimens is not necessary. Selective microscopic examination guided by relevant clinical history and macroscopic examination is a better option. This protocol will save money, time, and workload without compromising patient's safety and future management. However, a careful gross description is still necessary in certain cases for potential future medicolegal implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
5
28
1
2
Order By: Relevance
“…First, most research explored the clinical aspects, surgical techniques, and postoperative complications of LSG [6], with few studies examining the histopathologic outcomes, resulting in a scarcity of data about gastric histopathologic changes in LSG patients [7]. Second, while LSG patients may be presumed to have no significant gastric pathology, the literature is highly inconsistent as whether this is usually the case.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, most research explored the clinical aspects, surgical techniques, and postoperative complications of LSG [6], with few studies examining the histopathologic outcomes, resulting in a scarcity of data about gastric histopathologic changes in LSG patients [7]. Second, while LSG patients may be presumed to have no significant gastric pathology, the literature is highly inconsistent as whether this is usually the case.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, 8.4% of cases had unforeseen findings necessitating clinical follow-up [8]; in Kuwait, no normal specimens were reported, and 74.4% of the 656 LSG specimens had element/s of chronic gastritis [9]; and in New Zealand, >50% of the LSG specimens demonstrated histopathologic abnormality [10]. Conversely, others found that most post LSGs had no pathologic alteration, that a minority had significant pathologic findings [7, 11], and that routine microscopic examination of LSG specimens was unnecessary [6]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent prospective study by Abdullgaffar and colleagues [15] calls into question the utility of routine microscopic examination of all laparoscopic sleeve gastrectomy specimen. Based on < 1% incidence of benign lesions and no malignant lesions identified in 546 specimens, they advocate special gross handling protocols and meticulous macroscopic evaluation with selective microscopic examination only, for the benefit of cost and time effectiveness whilst demonstrating no major compromise to patient safety.…”
Section: Case Reportmentioning
confidence: 99%